Memahami Teori Pembelajaran - Jannah, Raihanil; Hamid, Abdul; S, Saprin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Education is a learning activity carried out by educational components to improve the potential of students in various ways. Learning theory is a collection of integrated principles that provide prescriptions for organizing learning situations or environments in such a way that they can help students achieve their learning goals easily. The types of theories used in learning are Behaviorist Theory, Cognitive Theory, Humanistic Theory, Constructivist Theory, and Social Learning Theory. Learning design is an activity that is designed to facilitate someone in the learning process with the aim that someone can be active in following it, so that mental and attitudinal changes can occur as expected due to these activities. Reform in education needs to be carried out in an effort to improve the quality of education and learning. Reform means radical change in an effort to improve the social, political, or religious fields in a society or country. People who carry out or think about reform are called reformers, namely people who advocate for non-violent improvement efforts.